2004
DOI: 10.3137/ao.420402
|View full text |Cite
|
Sign up to set email alerts
|

Downstream baroclinic development among forty‐one cold‐season Eastern North Pacific cyclones

Abstract: A quantification of local energy propagation is employed to distinguish cases of downstream baroclinic development, as described by Orlanski and Sheldon (1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Moreover, the use of the algorithm facilitates using a larger number of systems for the compositing in comparison to manual procedures used to create composites, for example, in Danielson et al . (2004) and Gan and Dal Piva (2016). For a regional analysis, the main genesis areas are identified and the tracks that have their genesis over a spherical region (radius = 10°) centred on the maxima genesis are selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of the algorithm facilitates using a larger number of systems for the compositing in comparison to manual procedures used to create composites, for example, in Danielson et al . (2004) and Gan and Dal Piva (2016). For a regional analysis, the main genesis areas are identified and the tracks that have their genesis over a spherical region (radius = 10°) centred on the maxima genesis are selected.…”
Section: Methodsmentioning
confidence: 99%
“…Orlanski and Sheldon (1995) observed that cyclone waves grow initially due to the upstream energy source and later because of the baroclinic conversion (EKE growing with ascent in the warm air and descent in the cold air) referred to as downstream baroclinic development. Motivated by this context, other authors have made use of the concept of downstream energy dispersion to provide a dynamical interpretation of the baroclinic disturbances based on observations (Chang, 1993; 2000; Danielson et al ., 2004; 2006; Decker and Martin, 2005; Dal Piva et al ., 2010; Rivière et al ., 2015) or model simulations (Simmons and Hoskins, 1979; Orlanski and Chang, 1993; Papritz and Schemm, 2013; Schemm et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies employing the K e framework (e.g., Danielson et al 2004;Decker and Martin 2005;Harr and Dea 2009;Cordeira and Bosart 2010) are based on analysis data, available at 10 and more pressure levels (referred to as vertical output resolution in the remainder). However, data from the operational ECMWF EPS is only available at nine pressure levels.…”
Section: A Datamentioning
confidence: 99%
“…In nature, individual storms tend to develop just downstream and slightly poleward of the maximum baroclinicity that may be quite localized, as discussed in . Frequently, downstream baroclinic development occurs resulting in a wavetrain along the major storm tracks (Danielson et al, 2004, and references therein). Since climatological basic states are averages of many instantaneous flow fields the local variations in baroclinicity are generally less than for instantaneous basic states.…”
Section: Structures Of Southern Hemisphere Cyclogenesis Modesmentioning
confidence: 99%